Enhancing organisation effectiveness through human, relational and structural capital: an empirical analysis / Amrizah Kamaluddin, Rashidah Abdul Rahman - Kamaluddin, Amrizah; Abdul Rahman, Rashidah (Accounting Research Institute (ARI) & Faculty of Accountancy, 2009)
The research deepens the understanding of the role of intellectual capital in creating corporate wealth from the perspective of a developing nation like Malaysia. A different economic set up where there exists different technological advancements (Chen, Cheng and Hwang, 2005) and differences in views on the metaphors of knowledge between the West and Asia (Andriessen and Boom, 2007) suggests that, a different implication of intellectual capital may exist. Thus, the research contributes to the intellectual capital literature of the ASEAN countries where culture, politics, economics and social environment provide a different perspective and challenges. Resource-based theory views, intellectual capital as the resources of wealth creation, vital to firm financial performance and the key driver to achieve sustained competitive advantages (Riahi- Belkaoui, 2003; Tayles, 2004).The current research investigates the relationship of Malaysian listed companies’ intellectual capital with organisation effectiveness. Based on the results through questionnaire survey of 155 Malaysian companies’ managers, it was found that among the intellectual capital components, structural and relational capital significantly influence the organisation’s effectiveness with structural capital as the strongest predictor. This reveals that structural capital, which comprises investment enhancement in technology, processes and systems, coupled with relational capital which includes customer-oriented and market driven activities, are imperative in determining high performance and competitive advantage